Chemical oceanography in the Cretan Sea: Changes associated to the transient - SOUVERMEZOGLOU, E.; KRASAKOPOULOU, E. (Mediterranean Marine Science, 2000)
The intensive research since 1985 in the framework of national and international programmes revealed important modifications in oxygen and nutrients distribution in the Cretan Sea. The significant increase of density and of formation rates of the Cretan Dense Water (CDW) during the last decade is basically responsible for the drastic change of the thermohaline circulation and the installation of a new hydrological regime in the Eastern Mediterranean. In the Cretan Sea, the most important effect of the new regime, is the installation of a well-defined "minimum salinity, temperature, oxygen and maximum nutrient" intermediate layer formed by the intrusion of the Transitional Mediterranean Water (TMW) compensating the massive CDW outflow. The nutrient enrichment of the intermediate layers of the Cretan Sea, due to the intrusion of the "nutrient rich-oxygen poor" TMW, was observed firstly in 1991 and became very important during 1994-95. During 1994-95 the TMW occupies the intermediate layers of the entire Cretan Sea and the concentrations of nutrients in this layer are often two times higher than in the past. Recently, in 1997-98 the chemical characteristics of TMW are less pronounced probably related to the weaker CDW outflow.